Communication P Systems on Simplicial Complexes with Applications in Cluster Analysis - Xiyu Liu; Alice Xue (Discrete Dynamics in Nature and Society)
The purpose of this paper is to propose a new kind of P systems on simplicial complexes. We present the basic discrete Morse structure, membrane structures on complexes, and communication rules. A new grid-based clustering technique is described based on this kind of new P systems. Examples are given to show the effect of the algorithm. The new P systems provide an alternative for traditional membrane computing.